Effect of combining exogenous fibrolytics enzymes supplementation with alkali and acid pre-treatments on wheat straw hydrolysis and ruminal fermentation - JABRI, JIHENE; ABID, KHALIL; YAICH, HELA; MALEK, ATEF; REKHIS, JAMEL; KAMOUN, MOHAMED (The Indian Journal of Animal Sciences, 2019)
The present study was undertaken to evaluate the efficacy of exogenous fibrolytics enzymes (EFE) to improve the in vitro cell wall hydrolysis, ruminal fermentation and digestibility of untreated (WS) and chemically pretreated wheat straw with NaOH (SWS), urea (UWS), and diluted H2SO4 (AWS). An in vitro gas production study during 96 h of incubation and an in vitro enzymatic hydrolysis during 20 h was conducted. The first EFE was a mixture (1:1, v/v) of cellulase and xylanase (Dyadic complex), applied at increasing doses (1, 2, 5 and 10 Î¼l/g DM). The second EFE (MaxFiber complex) was also applied at increasing dose (0.5, 1, 2 and 4 mg/g DM). The rate and the extent of the in vitro gas production (GP) of WS improved with both EFE supplementation especially with the optimal doses D1 and M2. In association with NaOH pre-treatment, the EFE failed to have any effect on wheat straw digestibility. In contrast, the urea pre-treatment seems to have a synergetic effect with EFE on ruminal utilization by accelerating the fermentation process. However, for AWS an antagonist effect was detected with both EFE. Moreover, the in vitro enzymic hydrolysis indicated a linear positive effect of EFE on reducing sugar release for almost all substrates and an increase in dry matter losses for only WS and AWS. These results revealed that the positive effect of EFE supplementation effect depended on the type of chemical pre-treatments and it was detected only for WS and UWS.